Knowledge of asthmatic children’s mothers regarding attack prevention and control - Guedes, Maria Vilaní Cavalcante; Lima, Luísa Helena de Oliveira; Carvalho, Ana Luisa Brandão de; Oliveira, Francisca Diana Mácia de (Rev Rene, 2005)
Descriptive study about health education and asthma whose objective is to evaluate what asthmatic children’s mothers know regarding the illness, getting to know how such mothers act when the asthma attack takes place, and identifying the implications of asthma for the children’s quality of life. The data were collected through the observation of forty mothers in a Children’s Public Hospital in Fortaleza-CE, structured interviews and simple observation at their homes. The results show that these mothers have little education and receive low wages, identify clearly the factors that trigger the attacks, but the children have at least one attack per month, which affects their quality of life. It was concluded that the mothers’ knowledge of the asthma control is fragmented and superficial, and that they do not employ this knowledge, contributing to increase the incidence of attacks and the consequent repercussion on the children’s low quality of life.